Beyblade X. Vol. 1 - Kawamoto, Homura; Muno, Hikaru (Viz Media, LLC, 2025)
Amateur Blader Robin Kazami is left without a team after a crushing defeat. Things start to look up when he runs into former Beyblade champion Jaxon Cross, who is on his own journey to fight back to the top of The X tower under the alias "Blader X." This unlikely duo teams up and vows to rise to the top of Beyblade.